Influence of various operating conditions on wastewater treatment in an AS-biofilm reactor and post-treatment using TiO2-based solar/UV photocatalysis. Issue 10 (29th April 2019) - Manu, D. S.; Thalla, Arun Kumar
ABSTRACT: In the present study, the effect of carbon to nitrogen (C/N) ratio, suspended biomass concentration ( X ), hydraulic retention time (HRT) and dissolved oxygen (DO) on chemical oxygen demand (COD) and nutrient removal from wastewater was investigated in a lab-scale activated sludge (AS)-biofilm reactor. Furthermore, in order to improve the quality of the treated wastewater, photocatalysis by TiO2 was investigated as a post-treatment technology, using solar and UV irradiations. The AS-biofilm reactor provided a substantial removal efficiency in terms of COD, ammonia nitrogen( N H 4 + − N ), total nitrogen (TN) and total phosphorous when the system was maintained at C/N ratio 6.66, X in the range 2–2.5 g/L, HRT 10 h, DO in the range of 3.5–4.5 mg/L and organic loading rate (OLR) of 0.96 kg COD/m 3  d during Run 1. Similarly, when the reactor was maintained at C/N ratio 10, X in the range of 3–3.5 g/L, HRT 8 h, DO in the range of 3.5–4.5 mg/L and OLR of 1.8 kg COD/m 3  d during Run 2. The microstructure of suspended and attached biomass comprised a dense bacterial structure of cocci and bacillus microorganisms. The UV photocatalysis was found to be better than solar photocatalysis during the comparative analysis. The maximum removal efficiencies of COD, most probable number and phosphorous at optimum conditions in the case of UV and solar irradiations were 72%, 95%, 52% and 71%, 99%, 50%, respectively.